Implementasi Pembelajaran Asynchronous Berbasis Project pada Mata Pelajaran IPS di Sekolah Dasar - Ilham, Muhammad (Institut Agama Islam Negeri Kendari, 2024)
This research examines the implementation and effectiveness of the asynchronous project-based learning model in Social Studies at the elementary school level. Using a mixed-methods approach, the qualitative aspect addresses the implementation process, while the quantitative aspect evaluates effectiveness through a pretest-posttest control group design. Conducted in the fifth grade of an Islamic elementary school, the study involves 36 students divided into experimental and control groups. Data is collected via observation, interviews, and learning outcome tests, analyzed using qualitative descriptive and inferential techniques. The study identifies five stages of asynchronous project-based learning: preparation, orientation, literation, collaboration, and presentation. The findings show that this learning model effectively enhances students' Social Studies outcomes. An independent sample t-test reveals a significant improvement in gain scores for the experimental group compared to the control group. Additionally, the average learning outcomes in the experimental group meet the class passing grade, confirming the model's effectiveness.KATA KUNCI: pembelajaran asynchronous, project, Ilmu pengetahuan Sosial